2016
DOI: 10.1089/jmf.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofArtemisia dracunculusAdministration on Glycemic Control, Insulin Sensitivity, and Insulin Secretion in Patients with Impaired Glucose Tolerance

Abstract: To evaluate the effect of Artemisia dracunculus on glycemic control, insulin sensitivity, and insulin secretion in patients with impaired glucose tolerance (IGT). A randomized, double blind, placebo-controlled clinical trial was performed in 24 patients with diagnosis of IGT. Before and after the intervention, glucose and insulin levels were measured every 30 min for 2 h after a 75-g dextrose load, along with glycated hemoglobin A1c (A1C) and lipid profile. Twelve patients received A. dracunculus (1000 mg) bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…HDL cholesterol levels increased. The results of the study showed that A. dracunculus herb extracts may in future be used as a therapeutic agent in the treatment of impaired glucose tolerance (Méndez-Del Villar et al, 2016).…”
Section: Hypoglycaemic Actionmentioning
confidence: 93%
See 2 more Smart Citations
“…HDL cholesterol levels increased. The results of the study showed that A. dracunculus herb extracts may in future be used as a therapeutic agent in the treatment of impaired glucose tolerance (Méndez-Del Villar et al, 2016).…”
Section: Hypoglycaemic Actionmentioning
confidence: 93%
“…It has preservative properties, so it is keenly used for pickling cabbage and cucumbers, marinating pumpkins, and for the production of tarragon mustard and herbal vinegars. It is recommended for people on a salt-free diet because it improves the taste of dishes (Kordali et al, 2005;Méndez-Del Villar et al, 2016;Çorapcı et al, 2020). It is also added to infusions, refreshing drinks, alcoholic and non-alcoholic drinks such as "Tarkhun"a carbonated, non-alcoholic drink, the main ingredient of which are fresh A. dracunculus leaves.…”
Section: Applications In the Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that this PMI-5011 A. dracunculus L. extract represents a promising botanical treatment for patients with diabetes. The most recent randomized, double blind, placebo-controlled clinical trial (NCT02330341) evaluating the effect of A. dracunculus on glycemic control, insulin sensitivity, and insulin secretion in patients with impaired glucose tolerance reported significantly decreased systolic blood pressure, glycated HbA1c, area under the curve of insulin, and total insulin secretion with a significant increase in HDL-C levels (Méndez-del Villar et al, 2016). …”
Section: Herbal Products and Secondary Metabolitesmentioning
confidence: 99%
“…Lately, there has been a growing interest on the biological activities of tarragon essential oils, extracts and dichloromethane extract active constituents in the literature. The results of the mentioned literature were showed that tarragon has various biological activities including the improving of Candida albicans infection [6], high antioxidant capacity [7], potent antileishmanial activity [8], strong antimicrobial activity [8], modulating of the immune system [9], effects on the glycemic control, insulin sensitivity and insulin secretion [10], analgesic and anti-inflammatory effects [11], antidiarrheal activity [12], anticancer effect [13], α-amylase and α-glucosidase inhibitory activities [14]. Russian tarragon and French tarragon are primary cultivars of A. dracunculus L. It is thought that the French tarragon is derived from Russian tarragon through the selection.…”
Section: Introductionmentioning
confidence: 99%